Validity of Mathematical Critical Thinking Ability Asessment Instruments - Rezi Ariawan; Nurmaliza Nurmaliza; Agus Dahlia; Hayatun Nufus; Erdawati Nurdin (Mathematics Education Study Program, 2022)
This study aims to produce an instrument for assessing mathematical critical thinking skills on material derived from algebraic functions that have been tested for validity. The form of research carried out is research and development and the development model used is a 4-D model (Define, Design, Develop, Disseminate). The research location is at SMAN 1 Tembilahan Hulu in the even semester of the 2021/2022 academic year. The object of research is an instrument for assessing mathematical critical thinking skills in class XI class derivatives of algebraic functions. The data collection instrument used an instrument validation sheet. Data analysis shows that the results of the validation of the mathematical critical thinking ability assessment instrument obtained an average value of the Aiken index of 0.811 with a very valid category and content validity with an average of 0.723 with a valid category. In terms of discriminating power, there are 2 questions with poor discriminating power and 6 questions that can be used to measure the level of students' mathematical critical thinking skills. So, it can be concluded that the development of an instrument for assessing mathematical critical thinking skills is to produce an instrument that has been tested for validity.